2021
DOI: 10.21203/rs.3.rs-149189/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene Expression and Alternative Splicing Dynamics Are Perturbed in Head Transcriptomes of Heterospecifically Mated Females

Abstract: Background Despite the growing interest in the female side of copulatory interactions, the roles played by alternative splicing mechanisms of pre-RNA and the epistatic effects of these interactions on tissues outside of the reproductive tract have remained largely unknown. Here we addressed these questions in the context of con- vs heterospecific matings between Drosophila mojavensis and its sister species, D. arizonae. We analyzed transcriptional responses in female heads using an integrated investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 9, 2021. ; https://doi.org/10.1101/2021.12.09.471925 doi: bioRxiv preprint Several studies have shown the importance of positive selection in the evolution of multigene families, especially in chemosensory genes such as ORs and GRs 84,85 . Positively selected chemoreceptors may be linked to adaptation in Drosophila species 86,87 . In the pea aphid, signatures of selection have been identified in chemosensory genes, including GRs and ORs, which may be implicated in the divergence of pea aphid host races [88][89][90] .…”
Section: Annotation Of Transposable Elements Enrichment Analysis and Selection Pressurementioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 9, 2021. ; https://doi.org/10.1101/2021.12.09.471925 doi: bioRxiv preprint Several studies have shown the importance of positive selection in the evolution of multigene families, especially in chemosensory genes such as ORs and GRs 84,85 . Positively selected chemoreceptors may be linked to adaptation in Drosophila species 86,87 . In the pea aphid, signatures of selection have been identified in chemosensory genes, including GRs and ORs, which may be implicated in the divergence of pea aphid host races [88][89][90] .…”
Section: Annotation Of Transposable Elements Enrichment Analysis and Selection Pressurementioning
confidence: 99%